Variant-specific surface proteins of Giardia lamblia are zinc-binding proteins. - Nash, T E (1993)
Giardia lamblia undergoes surface antigenic variation. The variant-specific surface proteins (VSPs) are a distinct family of cysteine-rich proteins. Characteristically, cysteine residues occur mostly as CXXC tetrapeptides. Four of the reported five VSPs contain a putative metal-binding domain that resembles other metal-binding motifs; the fifth is closely related but lacks an essential histidine. Three different native VSPs bound Zn2+. Co2+, Cu2+, and Cd2+ inhibited Zn2+ binding. Analysis of recombinant VSP fusion proteins showed that the putative binding motif bound Zn2+. Surprisingly, peptide fragments from other regions of the VSP contain numerous CXXCXnCXXC motifs that also bound Zn2+. Analysis of deduced amino acid sequences showed well-conserved CXXC spacing in three out of five VSPs, suggesting conservation of structure despite amino acid sequence divergence. The function of VSPs is unknown, but by binding Zn2+ or other metals in the intestine, VSPs may contribute to Zn2+ malnutrition or inhibition of metal-dependent intestinal enzymes, which would lead to malabsorption, a well-known consequence of giardiasis.